Bentuk Fatis dalam Wacana Lisan Percakapan Keluarga pada Masyarakat Melayu Jambi Provinsi Jambi - Ade Rahima; Irda Wahyuni (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This research aims to describe phatic forms in the oral text of family conversations in the Jambi Malay society at Kelurahan Pulau Temiang Kabupaten Tebo Jambi province. This study uses qualitative descriptive method, data collection techniques that are done with observation and recording. In this study, the data is in the form of phatic forms of the Jambi Malay language was taken from 2 families of 5 families who are native speakers of Jambi Malay in Kelurahan Pulau Temiang. Data are analyzed by using the distributional method. The results of this study show the forms of phatic of Jambi Malay in Kelurahan Pulau Temiang. It can be found there are three forms of phatic that include (1) phatic forms in the form of particles there are 30 data including 'kan', 'iyo', 'nak', 'dih', 'dek', (2) phatic in the form of the word there are 28 data including 'nelah', 'kan ko', 'kejaih', 'nonggok nelah', 'kalu', and (3) phatic in the form of phrases there are 2 data namely 'komsalam', 'salammelekom'.